Meat Hygiene and Health Hazard Awareness Among Butchers & Meat Retailers in Jammu - Rayees Ahmed Bafanda , Jahangir Ali; S. A. Khandi (Indian Journal of Extension Education, 2017)
The present study was conducted in Jammu district of Jammu and Kashmir State to analyze the meat associated health hazards’ awareness among butchers and meat retailers. Data was collected through a well structured interview schedule from three slaughterhouse (Ten butchers selected randomly selected per slaughter houses) and thirty meat retailers shops (one meat retailer selected from one shop). It was found that contact with infected person and improper meat handling was considered as a major risk for transmission of diseases by most of meat handlers. Poor awareness was found regarding different zoonotic diseases (except bird flu), which can be transmitted through meat handling. Meat handlers avoided the meat handling work only when suffered with major diseases. They were frequently wrong in judging the condition/diseases in which animals should not be slaughtered. The finding indicates that lapses exit between meat handlers’ decision and the scientifically correct decision and thus final decision about the fitness of carcass and offal’s must rest only with the veterinarian.